Enantio‐, Regio‐ and Chemoselective Copper‐Catalyzed 1, 2‐Hydroborylation of Acylsilanes. Issue 37 (30th May 2019) - Nagy, Audric; Collard, Laurent; Indukuri, Kiran; Leyssens, Tom; Riant, Olivier
Abstract: Enantioselective synthesis of synthetically significant (α‐hydroxyallyl)silanes, (α‐hydroxyaryl)silanes, and (α‐hydroxyalkyl)silanes is reported. The present copper‐catalyzed 1, 2‐selective hydroborylation of acylsilanes affords the aforementioned products in high yields and with high enantiomeric excesses. This robust and scalable additive‐free catalytic system relies on the use of low copper(II) acetate and diphosphine ligand loadings at room temperature in the presence of a commercially available and bench‐stable hydride source. Abstract : Want to 1, 2? α, β‐Unsaturated acylsilanes undergo 1, 2‐selective addition from hydride sources under the action of a copper/diphosphine catalytic system (see scheme). The optimization and scope of the reaction are presented. Synthetically useful α‐hydroxysilanes are obtained after a short reaction time under mild conditions.